QM AND AB INITIO INVESTIGATION ON THE HYDROGEN BONDING, NMR CHEMICAL SHIFTS AND SOLVENT EFFECTS ON THE DPPE - M. Monajjemi; A. Nouri; H. Monajemi (Universitas Gadjah Mada, 2007)
The hydrogen bonding effects that were produced from interaction of membrane lipid dipalmitoylphosphatidyl-ethanolamine (DPPE) with 1-5 water molecules, has been theoretically investigated through the quantum mechanical calculations at the Hartree-Fock level of theory and the 3-21G, 6-31G and 6-31G* basis sets with the computational package of Gaussian 98. According to the obtained results of the structural optimization of the isolated DPPE in the gas phase, we can see the evidences of interactions in the head group of this macromolecule (from the molecular point of view we have a proton transfer from the ammonium group to the phosphate oxygen of zwitterionic form. As we know that the hydrogen bonding of DPPE with water molecules which have surrounded its head group plays an important role in the permeability of DPPE. So, in order to understand the microscopic physico-chemical nature of this subject we have analyzed bond and torsion angles of DPPE before and after added water molecules. In this paper we have theoretically studied the complexes DPPE with water molecules which have surrounded its head group. As mentioned before, this theoretically study has been done through Hartree-Fock level of theory by using simple basis sets. Theoretical data shows that the interaction of head group of DPPE with water molecules causes some changes in the geometry of DPPE which were explained by the contribution of zwitterionic form of DPPE macromolecule, and finally hydrated DPPE becomes stable complex. Comparison between theoretical and experimental geometry data of DPPE macromolecule shows that the calculation at the HF/3-21 level of theory produces results which they are in better agreement with the experimental data. Moreover the hydrogen bonding effects on the NMR shielding tensor of selected atoms in the hydrated complexes of DPPE were reported. The